Weekly iron–folic acid supplements containing 2.8 mg folic acid are associated with a lower risk of neural tube defects than the current practice of 0.4 mg: a randomised controlled trial in Malaysia - Samson, Kaitlyn L. I .; Loh, Su Peng; Lee, Siew Siew; Sulistyoningrum, Dian C.; Khor, Geok Lin; Mohd Shariff, Zalilah; Isma, Irmi Zarina; Yelland, Lisa N.; Leemaqz, Shalem; Makrides, Maria; Hutcheon, Jennifer A.; Roche, Marion L.; et al. (BMJ Group, 2020)
Introduction Weekly iron-folic acid (IFA) supplements are recommended for all menstruating women in countries where anaemia prevalence is >20%. Anaemia caused by folate deficiency is low worldwide, and the need to include folic acid is in question. Including folic acid might reduce the risk of a neural tube defect (NTD) should a woman become pregnant. Most weekly supplements contain 0.4 mg folic acid; however, WHO recommends 2.8 mg because it is seven times the daily dose effective in reducing NTDs. There is a reluctance to switch to supplements containing 2.8 mg of folic acid because of a lack of evidence that this dose would prevent NTDs. Our aim was to investigate the effect of two doses of folic acid, compared with placebo, on red blood cell (RBC) folate, a biomarker of NTD risk. Methods We conducted a three-arm double-blind efficacy trial in Malaysia. Non-pregnant women (n=331) were randomised to receive 60 mg iron and either 0, 0.4, or 2.8 mg folic acid once weekly for 16 weeks. Results At 16 weeks, women receiving 0.4 mg and 2.8 mg folic acid per week had a higher mean RBC folate than those receiving 0 mg (mean difference (95% CI) 84 (54 to 113) and 355 (316 to 394) nmol/L, respectively). Women receiving 2.8 mg folic acid had a 271 (234 to 309) nmol/L greater mean RBC folate than those receiving 0.4 mg. Moreover, women in the 2.8 mg group were seven times (RR 7.3, 95% CI 3.9 to 13.7; p[removed]748 nmol/L, a concentration associated with a low risk of NTD, compared with the 0.4 mg group. Conclusion Weekly IFA supplements containing 2.8 mg folic acid increases RBC folate more than those containing 0.4 mg. Increased availability and access to the 2.8 mg formulation is needed. Trail registration number This trial is registered with the Australian New Zealand Clinical Trial Registry (ACTRN12619000818134).